Supplementation of Sapindus rarak and Garlic Extract in Feed Containing Adequate Cr, Se, and Zn on Rumen Fermentation - C H Prayitno; Y Subagyo; . Suwarno (Media Peternakan, 2013)
The objective of the study was to evaluate the effect of Sapindus rarak extract (SRE) with or without garlic extract (GE) on in vitro ruminal fementation. This research was conducted experimentally with a randomized block design, with 7 treatments and 5 blocks. The treatments were: R0:  dairy cow feed; R1: R0 + 1.5 ppm Cr + 0.3 ppm Se + 40 ppm Zn; R2: R1 + 1.8 g/kg methanol extract of lerak fruit  meal (SRE); R3: R2 + 0.25 ppm of garlic extract (GE); R4: R2 + 0.50 ppm of GE; R5: R2 + 0.75 ppm of GE; R6: R2 +1.0 ppm of GE. The results showed that the supplementation of SRE alone or without GE did not affect the pH, however, it decreased crude fiber digestibility. The supplementations of SRE and GE, decreased crude fibre digestibility as much as 13.01% up to 16.6%. The supplementation of 1.8 g/kg SRE + 0.25 ppm GE in the dairy cattle diet was able to decrease ace-tate, protozoal population and increase propionate. The supplementation of 1.8 g/kg SRE and 0.25 ppm garlic represents the best combination for dairy cattle feed in improving ruminal fermentation based on feed digestibility, fermentation products, and rumen bacterial population.